A methyl ketone bridged molecule as a multi-stimuli-responsive color switch for electrochromic devices. Issue 21 (25th April 2016) - Zhang, Yu-Mo; Xie, Fuli; Li, Wen; Wang, Yuyang; Zhang, Weiran; Wang, Xiaojun; Li, Minjie; Zhang, Sean Xiao-An
Abstract : A new multi-stimuli-responsive molecular switchM5 with a methyl ketone bridge has been developed to fabricate a visible-near infrared absorbing electrochromic device. Abstract : A new multi-stimuli-responsive molecular switchM5 with a methyl ketone bridge has been developed to fabricate a visible-near infrared absorbing electrochromic device. The basochromic and electrochromic properties of methyl ketoneM5 with nitronaphthalene were studied in detail using a spectroelectrochemical method and density functional theory (DFT) calculations. The colorlessM5 can be switched to green-yellow with broad visible-near infrared absorption (400–500 nm, 550–800 nm), stimulated by base and electricity. And a multi electron transfer–proton transfer mechanism (electrobase) of electrochromism forM5 has been proved using cyclic voltammetry (CV) and in situ UV-vis spectroscopy. This multi-stimuli-responsive color switch has been successfully applied in an electrochromic device with attractive properties such as short switching time and good reversibility.